The Combination of Novel Targeted Molecular Agents and Radiation in the Treatment of Pediatric Gliomas - Dasgupta, Tina; Haas-Kogan, Daphne (Frontiers in Oncology, 2013)
Brain tumors are the most common solid pediatric malignancy. For high-grade, recurrent or refractory pediatric brain tumors, radiation therapy (XRT) is an integral treatment modality. In the era of personalized cancer therapy, molecularly targeted agents have been designed to inhibit pathways critical to tumorigenesis. Our evolving knowledge of genetic aberrations in low-grade gliomas is being exploited with targeted inhibitors. These agents are also being combined with XRT to increase their efficacy. In this review, we discuss novel agents targeting three different pathways in low-grade gliomas, and their potential combination with XRT. B-Raf is a kinase in the Ras/Raf/MAPK kinase pathway, which is integral to cellular division, survival and metabolism. In low-grade pediatric gliomas, point mutations in BRAF (BRAF V600E) or a BRAF fusion mutation (KIAA1549:BRAF) causes overactivation of the MEK/MAPK pathway. Pre-clinical data shows cooperation between XRT and tagrgeted inhibitors of BRAF V600E, and MEK and mTOR inhibitors in the gliomas with the BRAF fusion. A second important signaling cascade in pediatric glioma pathogenesis is the PI3 kinase (PI3K)/mTOR pathway. Dual PI3K/mTOR inhibitors are poised to enter studies of pediatric tumors. Finally, many brain tumors express potent stimulators of angiogenesis. Several inhibitors of immunomodulators are currently being evaluated in in clinical trials for the treatment of recurrent or refractory pediatric central nervous system (CNS) tumors. In summary, combinations of these targeted inhibitors with radiation are currently under investigation in both translational bench research and early clinical trials. We summarize the molecular rationale for, and the pre-clinical data supporting the combinations of these targeted agents with other anti-cancer agents and XRT in pediatric gliomas. Parallels are drawn to adult gliomas, and the molecular mechanisms underlying the efficacy of these agents is discussed